Are some more equal than others? : English as a global and academic skill in Iceland - Freyja Melsted 1991- (2013)
In a world where global thinking is increasingly replacing the local, English has become the common language of globalization and international collaboration. The English language has spread to an extent that has never been seen before. For the Icelandic community this has a very significant effect on peoples’ daily lives, since it calls for specific language skills. I will analyze the spread of English and identify the challenges and opportunities it holds for Icelanders, especially within an academic environment at the University of Iceland. Studies show that good language skills put those that have them in an advantageous position over those that struggle with the extensive use of English. This general review of literature and recent studies on the linguistic situation in Iceland however reveal that even though using English can be a hindrance as well as an opportunity, students and educators both have to adapt to ongoing linguistic change.